2003
DOI: 10.1034/j.1600-0722.2003.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption from black tea and red wine onto in vitro salivary pellicles studied by ellipsometry

Abstract: The adsorption of black tea and red wine components onto a pellicle-like protein layer formed in vitro by adsorption from whole unstimulated saliva on hydroxyapatite discs were studied by in situ ellipsometry. It was found that components from black tea readily adsorbed to the pellicle. Subsequent exposure to saliva led to further adsorption of salivary components to give an overall increase in the amounts adsorbed. The amounts adsorbed increased still further following a third tea and saliva exposure. Compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 39 publications
5
65
1
4
Order By: Relevance
“…Statistically signifi cant diff erence was only found for red wine intake. Patients with tooth discolorations consumed less red wine than patients without discolorations, which is contrary to the previously mentioned studies reporting that highly pigmented beverages such as black tea and red wine cause extrinsic tooth discoloration [23][24][25] . Our fi ndings might be explained by the fact that wine stays in the oral cavity shorter than vegetables and therefore there is less opportunity for pigment formation 10 .…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Statistically signifi cant diff erence was only found for red wine intake. Patients with tooth discolorations consumed less red wine than patients without discolorations, which is contrary to the previously mentioned studies reporting that highly pigmented beverages such as black tea and red wine cause extrinsic tooth discoloration [23][24][25] . Our fi ndings might be explained by the fact that wine stays in the oral cavity shorter than vegetables and therefore there is less opportunity for pigment formation 10 .…”
Section: Discussioncontrasting
confidence: 54%
“…Other similar investigations pointed out that highly pigmented, acidic beverages not only caused tooth discoloration but also dissolution of the enamel [27][28][29][30] . Joiner et al also showed that black tea and red wine components had a profound eff ect on in vitro pellicle maturation while causing thickened layers of stained material to build up 23 . Extrinsic tooth staining can be caused by compounds that are incorporated into the pellicle and produce a stain consequently to their basic color (chromogen), or those that lead to staining caused by chemical interaction at the tooth surface, which is usually associated with cationic antiseptics and metal salts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that dietary chromogens in the drink are adsorbed to the pellicle, leading to a layer of stained material, which is not easily removed. 28 It has been shown that post bleaching, the susceptibility of enamel to red wine staining increases and post bleaching red wine causes greater staining than coffee. 29,30 Red wine also stains composite more than tea or coffee.…”
Section: Traumamentioning
confidence: 99%